The effects of GPER on age-associated memory impairment induced by decreased estrogen levels - Luo, Wenyu; Yan, Yudie; Cao, Yunpeng; Zhang, Yanbo; Zhang, Zhen (Frontiers in Molecular Biosciences, 2023)
Estrogen, as a pleiotropic endocrine hormone, not only regulates the physiological functions of peripheral tissues but also exerts vital neuroregulatory effects in the central nervous system (CNS), such as the development of neurons and the formation of neural network connections. In this context, it can positively stimulate spinogenesis and regulate synaptic plasticity and synaptic transmission to facilitate cognitive and memory performance, which require rapid estrogen-mediated reactions. These fast nongenomic effects can be initiated by membrane-bound estrogen receptors (ERs), known as ERα, ERβ, and G protein-coupled estrogen receptor (GPER). To date, ERα and ERβ have been well studied in age-associated memory impairment, whereas there is still a lack of attention to the role of GPER in age-associated memory impairment, and there are still disputes about whether GPER indeed functions as an ER to enhance learning and memory. In this review, we provide a systematic overview of the roles of GPER in age-associated memory impairment based on the expression, distribution, and signaling pathways of GPER, which might provide some inspiration to explore translational drugs targeting GPER for age-related diseases.